The research beamlines at the Dresden proton therapy facility: available infrastructure and experimental capabilities - Horst, Felix; Bodenstein, Elisabeth; Baumann, Michael; Beyreuther, Elke; Bokor, Jozef; Enghardt, Wolfgang; Gantz, Sebastian; Hejzlar, Martin; Kurth, Fritz; Meyer, Markus; Pieck, Stefan; Richter, Christian; et al. (Frontiers in Oncology, 2025)
The proton therapy facility in Dresden, Germany, has one treatment room equipped with a rotating gantry where patients are treated and an experimental room equipped with two horizontal beamlines for translational research. The present work describes the technical characteristics and provides measured beam data of these two complementary beamlines, one delivering scanned beams with quasi-clinical parameters and the other one stationary continuous and pulsed pencil beams with parameters exceeding the clinically used range. Features of the facility are the large scale of the experimental room enabling the development and installation of large devices and the parallel beam operation with the clinical room allowing irradiation experiments on weekdays and during daytime. An overview of past and ongoing physics and biology experiments performed at the facility by internal and external researchers from academia and industry is given, demonstrating its versatile experimental capabilities. This includes the development of novel proton therapy approaches and technology as well as elaborate in-vitro and in-vivo small animal experiments for which the necessary infrastructure is available in the same building.